THE INFLUENCE OF BRAND IMAGE, CONTENT MARKETING, PRODUCT QUALITY AND HEDONIC VALUE ON PURCHASE INTENTION FOR IPHONE PRODUCTS IN INDNESIA - Zelina Sofa Purnama; Arum Fito Pebrian (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This research aims to analyze the influence of brand image, content marketing, product quality, and hedonic value on purchase intention for iPhone products in Indonesia. The research used a quantitative approach with a structured survey involving 97 iPhone user respondents. Data were analyzed using validity, reliability, descriptive analysis and multiple regression tests. The research results show that product quality and hedonic value have a significant influence on purchase intention, while brand image and content marketing do not show a significant influence. Brand image in this research refers to consumer perceptions of the technology reputation, lifestyle and positive image of the iPhone. Content marketing is evaluated through the effectiveness of video content marketing on social media. Product quality is assessed from various aspects such as reliability, durability and performance. Hedonic value includes aspects of emotional satisfaction and consumers' personal experiences in using the iPhone. These findings provide insight for companies to focus on improving product quality in their marketing strategies to increase consumer purchasing intentions in Indonesia.